Serious game: Tracking school knowledge (Research, Society and Development, 2022)
This article presents a proposal to use the serious game "Trilhando Saberes Escolares", which aimed to contribute to a class, where the pedagogical intention would be to introduce the subject of a text to be worked later by students of a discipline of the postgraduate course. graduation of the Professional master’s in education, in the ABC Region. The objectives of the studies were: 1) To know the influences of international organizations (eg the World Bank) in the determination of public policies in education (eg the proposal of the full-time school) and 2) To reflect on the relationships between public policies, curriculum, school function and teacher training. It is a quantitative and qualitative research of a descriptive and interpretive nature, with characteristics of Design-Based Research, as proposed by Coob et al (2003). From a quantitative point of view, the variables Satisfaction and Social Interaction presented, in relation to the perception of knowledge acquisition, a correlation index of 0.874 and 0.885, respectively. Regarding qualitative data, in a global assessment, we can say that in the participants' view, the activity had a clear objective, was inviting and motivated them to mentally engage in the proposed activity. It is concluded that this research achieved the proposed objectives, which was to build and validate a serious game as a didactic resource to enhance the teaching and learning process. In this way, it will be possible to expand the possibilities of pedagogical actions in different educational contexts.